On the principles of building a model of a specialist – a graduate of a pedagogical university - K. S. Kаtаеv; S. G. Kаtаеv; I. V. Kаmenskaya (Образование и наука)
Introduction. Assessing students’ progress and predicting their future careers is paramount for any educational institution. The issue is particularly important for a teacher training institution, given the staff shortage in Russian schools and vocational education and training colleges. The educational process plays an important role in a graduate’s choice of future path, and hence, the problem of assessing the quality of this process arises as well.An option of solving this problem is to create a feedback system in the university, which allows evaluating the dynamics of students’ competency formation levels in the monitoring mode.Aim. The current research aims to develop and implement a multifactor competency model of a graduate of a pedagogical university, which can act as the basis for creating a system to monitor the quality of the educational process. The model takes into account psychological and socio-demographic factors, as well as students’ decisions in the field of a professional career.Methodology and research methods. The approbation of the proposed model was carried out on the data obtained as a result of the survey of students of Tomsk State Pedagogical University in 2021. The data were processed by conventional and multivariate statistical methods: factor and cluster analyses. The sample consisted of 189 students of all training courses of the Physics and Mathematics Faculty at Tomsk State Pedagogical University.Results. The analysis of the data obtained by using methods of multivariate statistics allowed the authors to obtain a variety of relationships between the factors taken into account. In particular, a pattern between the values of psychological scales, the level of competency formation and orientation of students in their choice of future profession was found.Scientific novelty. The block structure of the model makes it possible to analyse each block separately and together, selecting factors from different spaces, introducing new blocks or spaces of factors, oriented to the (possibly new) purpose of the study, without changing the others.Practical significance. The reasonableness of the obtained results of the study, the availability of a variety of algorithms for data interpretation indicate the real possibility of using in practice the proposed structure of the model, including the way of organising data as a monitoring system.